Transcriptome Analysis to Understand Salt Stress Regulation Mechanism of Chromohalobacter salexigens ANJ207 - Srivastava, Alok Kumar; Srivastava, Ruchi; Sharma, Anjney; Bharati, Akhilendra Pratap; Yadav, Jagriti; Singh, Alok Kumar; Tiwari, Praveen Kumar; Srivatava, Anchal Kumar; Chakdar, Hillol; Kashyap, Prem Lal; Saxena, Anil Kumar (Frontiers in Microbiology, 2022)
Soil salinity is one of the major global issues affecting soil quality and agricultural productivity. The plant growth promoting halophilic bacteria that can thrive in regions of high salt (NaCl) concentration have the ability to promote growth of plant in salty environment. In this study, attempts have been made to understand the salinity adaptation of a plant growth promoting moderately halophilic bacteria Chromohalobacter salexigens ANJ207 at genetic level through transcriptome analyses. In order to identify the stress responsive genes, the transcriptome sequencing of the C. salexigens ANJ207 under different salt concentration was carried out. Among the 8936 transcripts obtained, 93 were upregulated while 1149 were down regulated from 5 to 10 % NaCl concentration. At 10% NaCl, genes coding for lactate dehydrogenase, catalase and OsmC like protein were upregulated. On the other hand, when we compared 10 to 25 % salinity, 1954 genes were upregulated, while 1287 were downregulated. At 25% NaCl, genes coding for PNPase, potassium transporter, aconitase, excinuclease subunit ABC, transposase were found to be upregulated. The quantitative real time-PCR analysis showed the increase in the transcript of genes related to the biosynthesis of glycine betaine coline genes (gbcA, gbcB and L-pro) and in the transcript of genes related to uptake of glycine betaine (OpuAC, OpuAA and OpuAB). The transcription of the genes involved in the biosynthesis of L-hydroxyproline (proD and proS) and one stress response proteolysis gene for periplasmic membrane stress sensing (serP) were also found to be increased. The presence of genes for various compatible solutes and their increase in expression at high salt concentration indicated that a coordinated contribution by various compatible solutes might be responsible for salinity adaptation in ANJ207. The investigation provides new insights for functional roles of various genes involved in salt stress tolerance as well as oxidative stress tolerance produced by high salt concentration in ANJ207 and further support the notion regarding the utilization of bacterium, and their gene(s) in ameliorating salinity problem in agriculture.